The Influence Of Work Environment (Physical And Non-Physical) On Job Satisfaction Mediated By Work Motivation Of Employees Of Bank Bri Dago Bandung Branch - Prillia, Dira Devira; Marianti, Maria Merry (UNIVERSITAS PAKUAN, 2024)
This research explores the influence of the physical and non-physical work environment on job satisfaction with work motivation as a mediating variable at Bank BRI Dago Bandung Branch. The aim of the research is to identify the extent to which the work environment influences work motivation and job satisfaction and the role of work motivation in this relationship. The method used is path analysis by collecting data through questionnaires distributed to employees. The research results show that the physical and non-physical work environment has a significant influence on work motivation but does not have a direct impact on job satisfaction. Work motivation is proven to be a significant mediating variable in the relationship between both types of work environment and job satisfaction. In conclusion, although the physical and non-physical work environments do not directly influence job satisfaction, they both increase job satisfaction through increasing work motivation.